Cultural ambassadors with a cause: migrant musicians from lusophone Africa in Lisbon - Vanspauwen, Bart P. (2014)
Approaching music as a point of social connection in the postcolonial city of Lisbon, I seek to understand how migrant musicians from Portuguese-speaking African countries position themselves. Drawing on an ethnography carried out in the last 5 years, I argue that the contribution of these musicians to Portuguese expressive culture has not duly been recognized. However, these cultural ambassadors see music as a way of preserving their native cultural values and languages, and use Lisbon as a communicative space. They appeal to (supra)national institutions and governments for structural support and promotion, indicating that their contribution should be considered as an integral part of the cultural heritage of both Africa and Europe.